1) 6+29b
2)-8(2n+3)
3)2(-4+7z)
Пошаговое объяснение:
1)(10+22b)+(7b-4)= 10+22b+7b-4=(10-4)+(22b+7b)=6+29b
2)-(13n+11n)-(24-8n)=-24n-24+8n=-16n-24=-8(2n+3)
3)(14-2z)+(16z-22)=14-2z+16z-22=(14-22)+(-2z+16z)=-8+14z=2(-4+7z)
1. 6 + 29в
2. -(37 + 3n)
3. 2(7z - 4)
1) (10+22в)+(7в-4) = 10 + 22в + 7в - 4 = 10 - 4 + 29в = 6 + 29в
2) -(13+11n)-(24-8n) = -13 -11n - 24 + 8n = -37 - 3n = -(37 + 3n)
3) (14-2z)+(16z-22) = 14 - 2z + 16z - 22 = 14 - 22 + 14z = 14z - 8 = 2(7z - 4)
1) 6+29b
2)-8(2n+3)
3)2(-4+7z)
Пошаговое объяснение:
1)(10+22b)+(7b-4)= 10+22b+7b-4=(10-4)+(22b+7b)=6+29b
2)-(13n+11n)-(24-8n)=-24n-24+8n=-16n-24=-8(2n+3)
3)(14-2z)+(16z-22)=14-2z+16z-22=(14-22)+(-2z+16z)=-8+14z=2(-4+7z)
1. 6 + 29в
2. -(37 + 3n)
3. 2(7z - 4)
Пошаговое объяснение:
1) (10+22в)+(7в-4) = 10 + 22в + 7в - 4 = 10 - 4 + 29в = 6 + 29в
2) -(13+11n)-(24-8n) = -13 -11n - 24 + 8n = -37 - 3n = -(37 + 3n)
3) (14-2z)+(16z-22) = 14 - 2z + 16z - 22 = 14 - 22 + 14z = 14z - 8 = 2(7z - 4)